Upright kneeling position during second stage of labor: a pilot study - Dabral, Anjali; Pawar, Pallavi; Bharti, Rekha; Kumari, Archana; Batra, Achla; Arora, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Women delivering in upright position have shorter labour due to efficient and stronger contractions with faster descent of foetal head. The present study aimed to find out effect of upright kneeling position in the second stage of labour on maternal and foetal outcome and assess patients’ satisfaction. Methods: The study was carried out in a tertiary care hospital of North India from October 2012 to February 2014. Low risk women admitted in early labour were divided into two groups, women delivering in kneeling position and in supine position. The outcome measures studied were, duration of second stage of labour, mode of delivery, 2nd degree perineal tears, Apgar scores at 5 minutes, NICU admission rate and patient satisfaction. Results: The mean duration of second stage of labour in kneeling group was shorter by 14.901 minutes. The rate of vaginal delivery was comparable for both primigravidas and multigravida in kneeling and supine groups, RR: 2.275, 95% CI (0.7872-6.5831) and RR: 1.633, 95% CI (0.393-6.775). Primigravidas had more 2nd degree perineal tears in kneeling group as compared to supine, RR 4.191, 95% CI (1.54 to 11.41). No difference in Apgar scores >7 at 5 minutes was observed in both groups, however, significantly lesser babies in kneeling group were admitted in NICU, RR 0.246, 95% CI (0.079 to 0.761). There was no difference on comparing satisfaction scores of primigravidas and multigravida in both supine and kneeling position. Conclusions: Kneeling position reduces the duration of second stage of labour and NICU admissions.